Manipulating Gibberellin Control Over Growth and Fertility as a Possible Target for Managing Wild Radish Weed Populations in Cropping Systems - Groszmann, Michael; Chandler, Peter M.; Ross, John J.; Swain, Steve M. (Frontiers in Plant Science, 2020)
Wild radish is a major weed of Australian cereal crops. A rapid establishment, fast growth, and abundant seed production are fundamental to its success as an invasive species. Wild radish has developed resistance to a number of commonly used herbicides increasing the problem. New innovative approaches are needed to control wild radish populations. Here we explore the possibility of pursuing gibberellin (GA) biosynthesis as a novel molecular target for controlling wild radish, and in doing so contribute new insights into GA biology. By characterizing ga 3-oxidase (ga3ox) mutants in Arabidopsis, a close taxonomic relative to wild radish, we showed that even mild GA deficiencies cause considerable reductions in growth and fecundity. This includes an explicit requirement for GA biosynthesis in successful female fertility. Similar defects were reproducible in wild radish via chemical inhibition of GA biosynthesis, confirming GA action as a possible new target for controlling wild radish populations. Two possible targeting approaches are considered; the first would involve developing a species-specific inhibitor that selectively inhibits GA production in wild radish over cereal crops. The second, involves making crop species insensitive to GA repression, allowing the use of existing broad spectrum GA inhibitors to control wild radish populations. Toward the first concept, we cloned and characterized two wild radish GA3OX genes, identifying protein differences that appear sufficient for selective inhibition of dicot over monocot GA3OX activity. We developed a novel yeast-based approach to assay GA3OX activity as part of the molecular characterization, which could be useful for future screening of inhibitory compounds. For the second approach, we demonstrated that a subset of GA associated sln1/Rht-1 overgrowth mutants, recently generated in cereals, are insensitive to GA reductions brought on by the general GA biosynthesis inhibitor, paclobutrazol. The location of these mutations within sln1/Rht-1, offers additional insight into the functional domains of these important GA signaling proteins. Our early assessment suggests that targeting the GA pathway could be a viable inclusion into wild radish management programs that warrants further investigation. In drawing this conclusion, we provided new insights into GA regulated reproductive development and molecular characteristics of GA metabolic and signaling proteins.